Bacterial diversity and composition during rain events with and without Saharan dust influence reaching a high mountain lake in the Alps. Issue 6 (26th May 2014) - Peter, Hannes; Hörtnagl, Paul; Reche, Isabel; Sommaruga, Ruben
Summary The diversity of airborne microorganisms that potentially reach aquatic ecosystems during rain events is poorly explored. Here, we used a culture‐independent approach to characterize bacterial assemblages during rain events with and without Saharan dust influence arriving to a high mountain lake in the Austrian Alps. Bacterial assemblage composition differed significantly between samples with and without Saharan dust influence. Although alpha diversity indices were within the same range in both sample categories, rain events with Atlantic or continental origins were dominated by Betaproteobacteria, whereas those with Saharan dust intrusions were dominated by Gammaproteobacteria. The high diversity and evenness observed in all samples suggests that different sources of bacteria contributed to the airborne assemblage collected at the lake shore. During experiments with bacterial assemblages collected during rain events with Saharan dust influence, cell numbers rapidly increased in sterile lake water from initially ∼3 × 103 cell ml−1 to 3.6–11.1 × 105 cells ml−1 within 4–5 days, and initially, rare taxa dominated at the end of the experiment. Our study documents the dispersal of viable bacteria associated to Saharan dust intrusions travelling northwards as far as 47° latitude.